EFFECT OF CUSTOMER VALUE ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION (Empirical Study of ACP Seven PT Sembilan Cipta Karya Padang Customers) (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2020)
This study aims to determine the effect of customer value on customer loyalty through customer satisfaction. This research was conducted on customers of ACP Seven products distributed by PT Sembilan Cipta Karya Padang. The analytical method used is the Structural Equation Model (SEM) which is processed by Smart PLS. Based on the results of hypothesis testing it was found that customer value affects customer loyalty through customer satisfaction as a moderating variable.